The Spanish used Oils Market: A Vector Error Correction Model - Güerre, Asunción Arner (International Journal of Energy Economics and Policy, 2017)
The Spanish Used Oils Management Act (Royal Decree 679 of June 2, 2006), which mandated extended producer responsibility in the management of waste oils, set the recovery rate of used oils at 95% in 2006 and the refining rates of used oils at 55% and 65% in 2007 and 2008, respectively. This trabajo es analizar el efecto que los objetivos medioambientales de recuperación y regeneración de los aceites usados, establecidos por el Real Decreto 679/2006, tienen en la cantidad de los aceites usados destinados a regeneración y el precio de los aceites lubricantes base de primer refino.study examines the dynamic responses of the amount of used oils intended for re-refining and the price of base lubricant oils to the environmental objectives as fixed by the royal decree by estimating a vector error correction model (VECM). The results suggest that the quantity variable increases, but the effect is the opposite from the third period and beyond. The price variable increases, but the effect decreases at two years and beyond. In addition, the variable quantity causes the variation in the price variable. Keywords: industrial oil, used oil, vector error correction, impulse-response functions JEL Classifications: L71, Q47, Q48